SCREENING AND LARVICIDAL ACTIVITY OF THE ETHANOL ROOT AND LEAF EXRACT OF Combretum molle AGAINST Anopheles gambiae - D. , Kulawe; E. , Ezra; J. S. , Hena (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Mosquitoes are of public health importance as they constitute serious biting nuisance and transmit most deadly and life-threatening diseases. Plants have become the focus of intense study in terms of conservation and their pharmacological use. This study aimed at evaluating the larvicidal activity of stem extract of Combretum molle on Anopheles gambiae mosquito. The phytochemical analysis of the ethanol extract of the stem revealed the presence of biological active compounds including alkaloid, saponin, tannin, steroid and flavonoid. The effect of the ethanol extracts of the stem of Combretum molle (Bush willow) against the larvae of anopheles gambiae mosquito was further investigated in accordance to the World Health Organization’s guidelines for laboratory and field testing of mosquito larvicides (2005). Early second and third instars larvae of anopheles gambiae mosquitoes were exposed for up to 48 Hours to a concentration of 1, 25, 50 and 75ppm extracts of the roots and leaf. All tested extracts showed larval mortality, however, larval mortality was greatest with the ethanol leaf extract at an increasing concentration. This is supported by the abundance of flavonoid and tannin compound on the stem tissue. The study concluded that these parts of the Combretum molle contain larvicidal properties and could be implore as a natural larvicidal agent.